(untitled) (Fisioterapia e Pesquisa, 2009)
In physical therapy practice, it is assumed that lower-limb posture changes may influence other complexes' biomechanics or function during movement. However, literature on the relationship between static knee alignment and possible dynamic changes is still scarce and inconclusive. This study assessed the effect of static frontal knee alignment on plantar pressure distribution during gait. At first 44 young asymptomatic adults were evaluated. Front knee angles were measured by digital photogrammetry and classified as normal (170° to 175°), valgus ;175°. Given the low number of valgus found, two groups were analysed: normal knees (n=18) and varus knees (n=23). Plantar pressure distribution was measured during gait in five plantar surface areas. Groups were found to be statistically similar in all kinetic variables assessed in all plantar surface areas. Normal knees showed significant correlation with the contact time at lateral forefoot and midfoot. Varus knees showed correlation with contact area and time at respectively two and three plantar areas, and with full pressure at lateral forefoot. Results thus show that a 3° frontal knee malalignment, though with moderate correlation, does not influence pressure distribution on plantar surface during gait. It is hence suggested that clinical evaluation should not be limited to static knee assessment, but rather include dynamic activities.